The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3748/wjg.v25.i14.1741
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of non-alcoholic fatty liver disease in Chinese adult hypopituitary patients

Abstract: BACKGROUND Patients with hypothalamic-pituitary disease have the feature of central obesity, insulin resistance, and dyslipidemia, and there is increased prevalence of liver dysfunction consistent with non-alcoholic fatty liver disease (NAFLD) in this population. The causes of hypopituitarism in the reported studies varied and combined pituitary hormone deficiency including central diabetes insipidus is much common in this population. This retrospective cross-sectional study was performed to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
4
16
0
Order By: Relevance
“…Considering the underlying pituitary abnormalities, patients with PSIS often present with multiple pituitary hormone deficiencies. GH, TSH, ACTH, LH/FSH deficiency, and diabetes insipidus were present in 99.0%, 93.6%, 75.7%, 99.0%, and 9.7%, respectively, which agrees with the observations made by other studies 15,16 . The incidence of NAFLD based on abdominal ultrasonography was 50.5%, similar to that reported by Yuan et al 15 (54.0%) and slightly lower than that in other reports (70.7%–77%) 3,16,17 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Considering the underlying pituitary abnormalities, patients with PSIS often present with multiple pituitary hormone deficiencies. GH, TSH, ACTH, LH/FSH deficiency, and diabetes insipidus were present in 99.0%, 93.6%, 75.7%, 99.0%, and 9.7%, respectively, which agrees with the observations made by other studies 15,16 . The incidence of NAFLD based on abdominal ultrasonography was 50.5%, similar to that reported by Yuan et al 15 (54.0%) and slightly lower than that in other reports (70.7%–77%) 3,16,17 .…”
Section: Discussionsupporting
confidence: 90%
“…GH, TSH, ACTH, LH/FSH deficiency, and diabetes insipidus were present in 99.0%, 93.6%, 75.7%, 99.0%, and 9.7%, respectively, which agrees with the observations made by other studies 15,16 . The incidence of NAFLD based on abdominal ultrasonography was 50.5%, similar to that reported by Yuan et al 15 (54.0%) and slightly lower than that in other reports (70.7%–77%) 3,16,17 . The difference may be explained by the following reasons.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The prevalence of obesity and hyperlipidemia in patients with GH deficiency is high[ 7 ]. In addition, studies have found that the prevalence of nonalcoholic fatty liver disease (NAFLD) is high in patients with hypopituitarism, and the severity of GH deficiency is positively correlated with the severity of hepatic steatosis in NAFLD[ 8 , 9 ]. Interestingly, NAFLD develops quickly in patients with hypothalamic dysfunction or hypopituitarism[ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypopituitarism, which induces a condition similar to metabolic syndrome, is associated with NAFLD. We found that the NAFLD prevalence in patients with hypopituitarism (52.24%) was notably higher than that in the generation population (25%, reported in 2016) [15]; however, it was similar to that reported in Chinese adult patients with hypopituitarism (54%) [16]. More attention should be paid to NAFLD caused by hypopituitarism since such cases can rapidly progress to cirrhosis even at a young age [17].…”
Section: Discussionmentioning
confidence: 67%